Digital Twin for Sustainability Evaluation of Railway Station Buildings - Kaewunruen, Sakdirat; Xu, Ningfang (Frontiers in Built Environment, 2018)
The railway station is a primary asset of public transport systems and plays a crucial role in urban modernization. Most existing railway stations in the UK is historic and have been operated for many years. Maintenance and reconstruction are common concerns in the public railway industry, and clusters of information pertaining to this maintenance must be managed appropriately for effective outcome. Digital twin or BIM (Building information modeling) is a term frequently employed in the construction industry nowadays, because of its ability to provide wider and faster access to comprehensible and integrated information. A digital twin or a BIM is not only a tool, but also a process that can help to make changes in construction industry, which has remained unchanged for hundreds of years. This paper discusses a specific BIM application within the context of railway station buildings using a Revit-based simulation of construction work for King’s Cross station in London. The paper highlights the adoption and transformation of 3D model of the King’s Cross station building into a 6D building information model. The 6D model contains a time and cost schedule with carbon emissions calculation, and renovation assumptions using Revit. The outcome of this study can provide construction participants with reasonable guidance of BIM adoption on railway station projects that can be used for planning, designing and operating an economic and environmental efficient construction project.